2019
DOI: 10.1007/s40430-019-2078-z
|View full text |Cite
|
Sign up to set email alerts
|

Thin-walled metal deposition with GTAW welding-based additive manufacturing process

Abstract: The arc welding-based additive manufacturing technology is in its developing state. This technology can be utilized to produce free-form metallic structures for the aerospace and biomedical industry. The current article presents the design of semi-automatic gas tungsten arc welding-based additive manufacturing system for fabricating thin-walled metallic structures. This study aims to analyze the effect of process variables on the output parameters, such as deposition width and deposition height. The set of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The TIG welding process is highly energy-efficient and having less spattering defects with a higher deposition rate (Paskual et al, 2018). Therefore, the thin metal deposition with a relatively more deposition rate is possible with TIG welding-based process (Wang et al, 2020;Gokhale et al, 2019). Many of the authors have worked in the wire arc-based additive manufacturing processes on the optimization of the process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The TIG welding process is highly energy-efficient and having less spattering defects with a higher deposition rate (Paskual et al, 2018). Therefore, the thin metal deposition with a relatively more deposition rate is possible with TIG welding-based process (Wang et al, 2020;Gokhale et al, 2019). Many of the authors have worked in the wire arc-based additive manufacturing processes on the optimization of the process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [178] examined the influence of the heat accumulation on arc characteristics and metal transfer behavior during deposition in WAAM of Ti-6Al-4V parts. Gokhale et al investigated the effects of the arc current, the torch speed, the wire feed rate, and the torch angle on the formation of the bead to fabricate a thin wall structure using a WAAM process based GTAW [158,179]. They reported that the torch angle is a dominant parameter to determine the formation of the bead.…”
Section: Effects Of Deposition Parametersmentioning
confidence: 99%
“…The WAAM process is a promising technique for producing large-scale components and cost-effectiveness. There is three welding technology commonly applied in WAAM; gas metal arc welding (GMAW), gas tungsten arc welding (GTAW) [5], and plasma arc welding (PAW) [6]. However, conventional welding technology faced the issue of significant heat input, low surface quality, and low dimensional accuracy of WAAM components [7].…”
Section: Introductionmentioning
confidence: 99%